Line-of-sight velocities in a flaring active region - Kondrashova, N. (Кинематика и физика небесных тел, 2005)
Some spectra of a flaring active region were derived with the solar horizontal telescope ATsU-26 at the Terskol Observatory. Some properties of the photospheric velocity field of a bright plage are studied. The measurements of the line-of-sight velocity are made in the Fraunhofer lines Fe I λλ 630.25 nm, 630.35 nm and Ti I λ 630.38 nm. Temporal variations of the line-of-sight velocities at photospheric levels of 203, 240, and 515 km of the plage were obtained. Motions directed to an observer dominate on a considerable part of the plage. At the edge of the plage there is a flow from the observer at a photospheric level of 203 km.